The creation of synthetic life from scratch: Future reality or unattainable possibility? - Gómez Gómez, José María (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The origin of Life is one of the fundamental mysteries still unsolved by the modern science. The actual dominant orthodox scientific paradigm in Biological Sciences has as fundamental tenets that Life is a natural phenomenon as well as that the origin of Life would be an understandable event. Life apparently does not require of supplementary «vital principles» transcendent to the physical-chemical laws («materialistic forces») that govern non-living phenomena. No supernatural causes are required to explain Life. Here I have called this vision the mechanistic vital-less paradigm of Life. On the contrary the Vitalism is an old and discredited doctrine, which sustains that Life is a singular phenomenon that requires of the action of «vital forces» exclusives to living domain. The recent creation of a bacterial chromosome by Craig Venter’s team and the successful transfer of it into a bacterium, where the native DNA has been replaced, has created the expectation of the creation of synthetic Life (SLife-Lab) from scratch could be a reality in the next years. However, despite this scientific notable milestone, the dream of the creation of autonomous SLab-Life (the so-called a second origin) has not been realized yet. Thus, in my opinion, an open question that still remains is this: Why it has not been SLab-Life created yet? Another question related to the previous is: Is Vitalism an idea completely dead? Here, I discuss these issues taking account a historical perspective